Mythical moments in Remington brand history. Issue 1 (1st January 2016) - Witkowski, Terrence H.
Abstract : To investigate the brand history of Remington firearms, this study introduces and applies a new construct, the 'mythical moment', which is defined as an episode when the course of brand mythmaking quickens and has greater cultural resonance. Three such mythical moments are examined: the Remington founder myth of 1816, the Remington sharpshooter myth of the 1870s, and the mythic world of Remington storefront windows in the early twentieth century. These narrative histories are analyzed in terms of their commonalities and differences, and their implications for processes of heritage branding and brand consumption are discussed.